Comparative Analysis of Pension Funds with Single Interest Model and Compound Interest Model - Septiandari, Thariza Haifa; Akbar, Muhammad Rizky Umaran (iora, 2025)
This study aims to provide a basic analysis of pension fund calculation using a simple interest model. In this study, we assume a fixed contribution invested at a fixed interest rate during the retirement period of the retiree. Using the basic formula of simple interest accumulation, we calculate the final amount available at retirement. The results show that even with low interest rates, wealth accumulation can increase significantly with long-term planning. This study is expected to provide readers with an initial understanding of the importance of pension fund planning.